(untitled) (Research, Society and Development, 2020)
This article aims to present, through a narrative review of the literature, the objectives of treatment of Scheme Therapy (ST) for patients with Narcissistic Personality Disorder (NPD) and for the functioning of each predominant Schematic Mode (SM) in NPD. The search for data for the construction of this article was through consultations on national and international digital platforms, and also used authors that are references of NPD and ST. As a result, it was found that the predominant SM in patients with this type of disorder are the Lonely Child Mode, the Self-Magnifying Mode, the Provocative and Attack Mode, the Protected-Disconnected Mode and the Self-Relief Mode. When discussing the treatment goals for each modality, it was concluded that, based on the techniques used by the therapist, the objective of ST for NPD, is to strengthen the Healthy Adult Mode, so that the patient can adapt more adaptive and functional guidelines in his daily life.